Determining the non-pharmacological methods using to cope with radiationrelated oral mucositis in patients with head and neck cancer. - Toygar, Ismail; Yeşilbalkan, Oznur Usta (Nursing Practice Today, 2019)
Background & Aim: The radiation-related oral mucositis is common in patients with head and neck cancer. Patients trying pharmacological and non-pharmacological methods to cope with oral mucositis. In this study, it was aimed to determine the nonpharmacological methods in dealing with oral mucositis of head and neck cancer patients. Methods & Materials: In this descriptive study, the data were collected from a University Hospital's radiotherapy unit and a special cancer treatment center between June 2017 and October 2018. The study included 108 individuals aged 18 and over, who were diagnosed with head and neck cancer, could be communicated verbally and accepted to take part in the study during the study period. A convenience sample of patients was obtained from among all patients meeting the criteria for inclusion. A 20-item questionnaire (including the sociodemographic items, risk factors, oral mucositis history, and non-pharmacological methods) form developed by researchers were used in the study. The written permissions were obtained from the Ethics Committee of Ege University, Faculty of Nursing, the centers that research conducted and the participants. IBM Statistical Package for Social Science for Windows package program version 25.0 was used for analyzing the data. Results: Of the 108 individuals included in the study, 64.8% (n=70) were male. The mean age of the participants was 59.73±8.92. It was found that 58.3% (n=63) of the participants had mouth problems after starting treatment. 69.8% of the individuals who developed oral mucositis used a non-pharmacological method to cope with oral mucositis. The most commonly used non-pharmacological method was the mixture of carbonate and salt with 60.7%. The second most common method was black mulberry syrup with 37.7%. Other methods were including propolis, mulberry syrup, raspberry syrup, tea tree oil, thyme, and sumac. Conclusion: While some methods used by the patients were effective, the others were ineffective. Health professionals, especially nurses, requirement be informed about the non-pharmacological methods, therefore, they can guide the patients about using the right methods.